PENGARUH AMBIGUITAS PERAN, TINGKAT PENDIDIKAN DAN OVERLOAD ROLE TERHADAP KEINGINAN BERPINDAH PADA AUDITOR KANTOR AKUNTAN PUBLIK DI JAKARTA DAN SEMARANG - Iis Duwinaeni (Fakultas Ekonomi Universitas Pekalongan, 2018)
This study aims to analyze the influence of role ambiguity, educational level and overload role to turnover intention. The object of research is public auditor in Jakarta and Semarang. This research is an empirical research respondents as much as 53 respondents in 2017 . Data analysis with multiple regression was done by using spss program. The results of this study indicate that Role Ambiguity has and significance to turnover intention, Level of education effect and significant to turnover intention, Overload role effect and significant to turnover intention.Keywords: Auditor, Role Ambiguity, Education Level, Overload Role, Turnover Intention.